D2 statistical analysis of yield contributing traits in maize (Zea mays L.) inbreds (Bangladesh Journal of Botany, 2018)
Investigation was carried out to determine the genetic divergence in the 25 maize inbred lines. Analysis of variance revealed highly significant differences among all the inbreds. Inbreds were grouped into five clusters, indicating the presence of genetic diversity. The clusters I, IV and V had the highest number of inbreds (6). The maximum inter-cluster distance was observed between clusters I and III (19.279) and the highest intra-cluster distance was recorded in cluster III (0.243) and also wide range of variation was observed in cluster mean performance for the characters studied. Intercrossing among the inbreds belonging to clusters II and III was suggested to develop high yielding inbreds with desirable characters.